Lingkar Pinggang Sebagai Faktor Risiko Utama Osteoartritis Lutut dan Peran Penting Depresi - Felicia, Tesya; Kristian, Kevin; Handajani, Yvonne Suzy; Barus, Jimmy Fransisco Abadinta (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Background: As the elderly population increases, the incidence of osteoarthritis (OA) also rises. In Indonesia, the prevalence of OA is 15.5% in men and 12.7% in women. Research on OA in Indonesia remains limited, particularly regarding population-based studies. Purpose: This study aimed to provide an overview of knee OA and its risk factors among older adults living in Pusaka Kebon Jeruk, West Jakarta. Methods: This cross-sectional study involved 100 respondents. Data were collected through interviews using questionnaires. Bivariate analysis was conducted using chi-square tests, and multivariate analysis was performed using multiple logistic regression (p<0.05). Results: The study found that 28% of the elderly had knee OA, with the majority aged 60-74 years (75%), female (71%), unemployed (82%), educated for 12 years or more (90%), and married (55%). Bivariate analysis identified waist circumference (p<0.001) and depression (p=0.032) as variables significantly associated with knee OA. Multivariate analysis indicated that waist circumference was the most significant factor affecting knee OA, with an odds ratio (OR) of 24.239. The prevalence of knee OA requires serious attention from the government and healthcare providers. Conclusion: Knee OA is significantly related to waist circumference and depression, with waist circumference being the most critical factor. Central obesity is associated with a higher risk of knee OA. Therefore, it is essential to prevent central obesity through a balanced diet and regular exercise.